2014
DOI: 10.1007/s40618-014-0140-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between serum omentin-1, body fat mass and bone mineral density in healthy Chinese male adults in Changsha area

Abstract: Serum omentin-1 was negatively correlated with FBM and BMI in healthy Chinese male adults, It was not significantly correlated with bone turnover biochemical markers. Omentin-1 may exert ambiguous effects on BMD, which maybe caused by the complex interactions among adipokines, hormonal activity, and body composition and bone metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…It has been determined that omentin enhances insulin-stimulated glucose uptake in adipose tissue and many studies have shown that omentin is negatively correlated with BMI and fat mass, insulin resistance and metabolic syndrome [33,34]. Our data are partially in agreement with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…It has been determined that omentin enhances insulin-stimulated glucose uptake in adipose tissue and many studies have shown that omentin is negatively correlated with BMI and fat mass, insulin resistance and metabolic syndrome [33,34]. Our data are partially in agreement with these findings.…”
Section: Discussionsupporting
confidence: 91%
“…A similar correlation was also found in girls with anorexia nervosa [17]. Li et al [21] also reported that omentin-1 was negatively correlated with BMD in healthy men, but this correlation disappeared after adjustment for age and BMI. However, Assadi et al observed a positive association between omentin-1 and BMD in patients with multiple sclerosis [18].…”
Section: Discussionsupporting
confidence: 70%
“…The majority (89 %) of women in the study had vitamin D levels below reference values ( ≥ 25 ng/dL). We categorized all women according to their vitamin D levels as serious deficiency (0-9.9 ng/ mL), moderate deficiency (10-24.9 ng/mL), and normal level (25-80 ng/mL) [21]. The percentage of women with normal vitamin levels was 7 in the control group, 10 in the menopausal group, and 15 in the osteoporotic group (▶ table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that omentin-1 is inversely correlated with BMI [2,6,12,14,15,[26][27][28]34,35], FM, TFM, and fat percentage [35]. Additionally, Pearson's correlation and partial correlation coefficients showed no significant correlations between omentin-1 and adiposity.…”
Section: Discussionmentioning
confidence: 84%